Makna Ungkapan Adat dalam Upacara Kawen Gate Masyarakat Desa Boru Kedang Kecamatan Wulanggitang - Kedang, Yuliana Gekeng; Pande, Rikardus; Yolanda Mario Leu, Yoakim (Social Science Academic, 2023)
This research article aims to describe the meaning in the expression marriage gate in Boru Kedang Village, Wulanggitang District. The kawen gate ceremony or traditional marriage uses traditional expressions as a distinctive language that contains useful meanings that show community identity. This study uses the basis of semantic theory. The method used is a qualitative method with a qualitative descriptive approach. The research data is oral data in the form of expressions in the kawen gate ceremony. Sources of data for informants are traditional leaders. Data collection was carried out by interviewing and documentation techniques. Data analysis uses data selection techniques, data presentation, and conclusion drawing. Data processing using research results. The meaning of traditional expressions in the traditional kawen gate ceremony in Boru Kedang, Wulanggitang District, East Flores Regency, consists of denotative meaning and connotative meaning, namely (1) denotative meaning in the expression of the stages of baung basa (know the house), (2) denotative meaning in the expression of the stages of bataan biat (return visit), (3) denotative meaning of the expression in the stages of pana laran tadan kila (exchanging rings), 4) denotative meaning of the expression in the stage of wua malu gere (penghataran belis), (5) denotative meaning of the expression at the stage of dokang turu (delivering the bride to the aisle), (6) the connotative meaning of the expression of the stages of baung basa (know the house), and, (7) kusang hebo (washing hair).